Coir Fibre-Low Density Polyethylene Composite As A Packaging Material - A.Talib, Rosnita (2002)
The overall goal of current research was to produce a polymer composite consisting of coir fibre (CF) ie. coconut palm fruit fibre and low density polyethylene (LDPE) that would be suitable for food packaging application. CF and LOPE coupled with and without maleated polyethylene ( MAPE) materials have been compounded using a twin screw extruder. The mechanical and physical properties of both composite systems were compared. The effect of fibre and MAPE loading on those properties have also been analyzed. In addition, maleated polyethylene with two different molecular weight (M,,) but having the same acid number have also been incorporated into composites to study the effect of molecular weight on the properties of composites. The incorporation of CF into LOPE matrix has resulted in the positive improvement in the tensile and flexural strength and moduli. Whereas, unnotched impact strength (IS), density, water absorption and thickness swelling decreased as the fibre loading was increased. It was observed that the tensile and flexural strength, unnotched is and elongation at break of composites have been improved almost doubled that of uncoupled composite. The dimensional stability of composites had also improved after addition of MAPE. Mechanical and physical properties of composites were found to depend strongly on the M" and sufficient maleic anhydride content of the functionalized polyethylene. Environmental scanning electron microscopy (ESEM) displayed that the adhesion between fibre and matrix had been improved at interfacial region. The ESEM micrographs exhibited evidence that an even fibre distribution might play a dominant role on the properties.